The Serum Cytokine Panel Predicts Cardiac Outcomes Following Acute Myocardial Infarction: Serum Cytokine Predicts Cardiac Outcomes - Tai, Sichao (Journal of Medical Biochemistry, 2026)
Background: While individual cytokines have been implicated in the pathogenesis of acute myocardial infarction (AMI), the predictive utility of a comprehensive serum cytokine panel for post-infarction outcomes remains underexplored. Methods: We conducted a prospective cohort study of 184 patients presenting with ST-segment elevation myocardial infarction (STEMI). Blood samples were collected within 24 hours of primary percutaneous coronary intervention (PCI). A panel of 11 cytokines (GDF-15, IL-1β, IL-6, IL-8, IL-10, IFN-γ, VEGF, G-CSF, GM-CSF, TGF-β, and hs-cTnT) was analyzed using multiplex bead-based immunoassay. The primary endpoint was the occurrence of Major Adverse Cardiac Events (MACE) at 12 months, defined as cardiovascular death, recurrent MI, or heart failure hospitalization. Results: Elevated levels of IL-6, IL-8, GDF-15, and hs-cTnT were significantly associated with 12-month MACE. Multivariable logistic regression identified GDF-15 (OR 3.58, 95% CI 1.82–7.04, p<0.001) and hs-cTnT (OR 2.94, 95% CI 1.53–5.65, p=0.001) as independent predictors. A composite biomarker score demonstrated an AUC of 0.86 (95% CI 0.80–0.92) for predicting MACE. Conclusion: A specific serum biomarker profile, particularly involving GDF-15 and hs-cTnT, independently predicts adverse outcomes post-MI. Routine biomarker profiling may enhance risk stratification beyond traditional clinical variables.